2010
DOI: 10.1002/geot.201000033
|View full text |Cite
|
Sign up to set email alerts
|

Swelling of sulphatic claystones – some fundamental questions and their practical relevance /

Abstract: Sulphatic claystones exhibit a heavily swelling behaviour and are among the most problematic rocks for tunnelling. Their swelling is usually attributed to the transformation of anhydrite to gypsum. The paper questions this simplistic hypothesis through a qualitative discussion of the processes underlying the phenomena that are observed macroscopically, and by identifying a series of fundamental issues that are important from the point of view of tunnel design. At the same time, it provides an overview of ongoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(17 citation statements)
references
References 8 publications
0
16
0
1
Order By: Relevance
“…In the neighbouring town, this resulted in a ground uplift of B26 cm and differential movements causing serious cracking in many buildings 12 . The same process also poses severe issues in tunnelling and mining, causing some tunnels to be periodically closed for rehabilitation because of excessive floor heave 13 .…”
mentioning
confidence: 99%
“…In the neighbouring town, this resulted in a ground uplift of B26 cm and differential movements causing serious cracking in many buildings 12 . The same process also poses severe issues in tunnelling and mining, causing some tunnels to be periodically closed for rehabilitation because of excessive floor heave 13 .…”
mentioning
confidence: 99%
“…Results showed that the geothermal wells hydraulically connected anhydrite-bearing clay rocks with a deeper aquifer, and resulting water inflow into the anhydritic clay rock triggered the transformation of the mineral anhydrite into gypsum (Ruch 30 and Wirsing, 2013). This chemical reaction is accompanied by a volume increase that leads to rock swelling, a phenomenon typically encountered in tunneling in such rock (e.g., Einstein, 1996;Anagnostou et al, 2010;Butscher et al, 2011bButscher et al, , 2015Alonso, 2012), bur recently also observed after geothermal drilling (Butscher et al, 2011a;Grimm et al, 2014). The above 2 Solid Earth Discuss., doi: 10.5194/se-2016-174, 2017 Manuscript under review for journal Solid Earth Published: 10 January 2017 c Author(s) 2017.…”
Section: Study Sitementioning
confidence: 89%
“…The generation of stress due to confined crystallization is a subject that has received considerable attention by authors with engineering applications in mind. The crystallization of salts is a well-documented source of deterioration in building stones (e.g., Li, 2017;Novak & Colville, 1989), tunnel walls (Anagnostou et al, 2010), and oil and gas wellbores (e.g., Ghofrani & Plack, 1993;Wolterbeek et al, 2017). Crystallization in these types of environments frequently occurs in unsaturated conditions, where both a fluid and a vapor phase are present in pores.…”
Section: Introductionmentioning
confidence: 99%